2017
DOI: 10.1371/journal.pone.0169732
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation Changes in the Permafrost Regions of the Qinghai-Tibetan Plateau from 1982-2012: Different Responses Related to Geographical Locations and Vegetation Types in High-Altitude Areas

Abstract: The Qinghai-Tibetan Plateau (QTP) contains the largest permafrost area in a high-altitude region in the world, and the unique hydrothermal environments of the active layers in this region have an important impact on vegetation growth. Geographical locations present different climatic conditions, and in combination with the permafrost environments, these conditions comprehensively affect the local vegetation activity. Therefore, the responses of vegetation to climate change in the permafrost region of the QTP m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…We found that the breakpoints of TP temperature during 1982-2013 at different time scales largely occurred between 1994 and 1998 (Figures 2-6). This result is not only closer to direct NDVI segmentation investigation on the TP [52], but it is also closer to the artificial breakpoint of 2000 years in some investigations of TP NDVI response analysis [39,46]. Nevertheless, our results strongly imply that the artificial abrupt points later than 2000 may bring greater bias in TP NDVI response analysis.…”
Section: Discussionsupporting
confidence: 87%
“…We found that the breakpoints of TP temperature during 1982-2013 at different time scales largely occurred between 1994 and 1998 (Figures 2-6). This result is not only closer to direct NDVI segmentation investigation on the TP [52], but it is also closer to the artificial breakpoint of 2000 years in some investigations of TP NDVI response analysis [39,46]. Nevertheless, our results strongly imply that the artificial abrupt points later than 2000 may bring greater bias in TP NDVI response analysis.…”
Section: Discussionsupporting
confidence: 87%
“…An increasing number of studies, which have benefitted greatly from the accumulation of more than a decade of satellite observations, have focused on photosynthetic metabolism over the TP (Lehnert et al, ). The central issues, which have been investigated widely in prior studies, are the changes that are actually occurring and the mechanisms underlying these changes (Shen, Piao, Cong, et al, ; Wang et al, ). However, our current understanding is quite limited in the following aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Islands of permafrost and seasonally frozen soil are mainly distributed in the LRHR and YERHR (Mao et al, 2016). The lower altitude, the warmer and more humid climate, and higher vegetation cover lead to higher SWC and ST in the southeast areas than those in the northwest (Cuo et al, 2015; Wang, Wang, et al, 2017). Moreover, the existence of permafrost restricts the water and heat exchange between the atmosphere and the ground, making them both relatively low (Chang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%